2001
DOI: 10.1364/ol.26.000066
|View full text |Cite
|
Sign up to set email alerts
|

Compact, 220-ps visible laser employing single-pass, cascaded frequency conversion in monolithic periodically poled lithium niobate

Abstract: We report the first demonstration to our knowledge of 220-ps visible laser generation from passively Q-switched-laser pumped periodically poled lithium niobate (PPLN) in a single-pass, cascaded frequency-conversion process. The monolithic PPLN consists of a 1-cm section for frequency doubling the 1064-nm Nd:YAG pump laser to a 532-nm laser and a subsequent 4-cm section for generating the visible laser in a 532-nm-pumped optical parametric generation (OPG) process. In generating the 622.3-nm OPG signal waveleng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Among all of the QPM crystals, periodically poled lithium niobate (PPLN) [8][9][10] is particularly attractive due to its availability as a large crystal, its large nonlinear coefficient, and its broad transparent range. Moreover, multi-periodically poled fabrication makes it feasible for several parametric processes to be performed simultaneously in a monolithic PPLN [11][12][13] at a certain phase-matching temperature. Thus a large range of wavelengths can be obtained from a single-pass process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among all of the QPM crystals, periodically poled lithium niobate (PPLN) [8][9][10] is particularly attractive due to its availability as a large crystal, its large nonlinear coefficient, and its broad transparent range. Moreover, multi-periodically poled fabrication makes it feasible for several parametric processes to be performed simultaneously in a monolithic PPLN [11][12][13] at a certain phase-matching temperature. Thus a large range of wavelengths can be obtained from a single-pass process.…”
Section: Introductionmentioning
confidence: 99%
“…Chiang et al reported visible laser generation through cascaded second-harmonic generation (SHG) and OPG in a monolithic PPLN, with 16% overall efficiency at two times the threshold. [11] From a periodically poled lithium tantalate with multi-domained modulation, Gao [14] and Xu et al [15] demonstrated red-green-blue laser generation through cascaded OPO-SFG, with a green-to-white light power con-version efficiency of about 30%. In contrast with the cascaded OPO and SFG, single-pass OPG and SFG requires no resonator mirrors or coatings, and the size and cost of the setup could be somewhat lower.…”
Section: Introductionmentioning
confidence: 99%
“…The quasi-phasematching (QPM) technique opened a new window for enhancing the conversion efficiency, since it allows one to use the largest nonlinear coefficient of a crystal with noncritical phasematching. Among several available periodically poled crystals such as LiNbO 3 (PPLN) [19,20], stoichiometric LiTaO 3 (PPSLT) [21], and KTiOPO 4 (PPKTP) [22,23], the first one has the highest nonlinearity (d eff ≈ 14 pm/V). Moreover, doping of PPLN with MgO significantly increases the threshold of photorefractive damage at room temperature, allowing the crystal to reach more than 50% conversion efficiency in continuous wave (CW) intracavity frequency doubled Nd:YVO 4 laser [24].…”
Section: Introductionmentioning
confidence: 99%
“…A fruitful approach to generate short visible pulses is to use a master oscillator power amplifier system operating in the near-infrared and to use non-linear processes to reach the visible range. Recent developments in passively Qswitched microchip lasers [1,2] open the way to a large number of studies on very compact and efficient pulsed sources [3][4][5][6][7]. Nevertheless, the repetition rates of the published devices are almost always in the kilohertz range.…”
mentioning
confidence: 99%
“…In this purpose we chose a periodically-poled lithium niobate crystal (PPLN) because of its exceptionally high effective non-linear coefficient of 17 pm/V. Such PPLN-based OPG configurations had already been successfully investigated in the ns regime with low repetition rates [5][6][7]. The PPLN crystal was 3 cm-long and consisted in 5 parallel gratings.…”
mentioning
confidence: 99%